2005
DOI: 10.1084/jem.20041057
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of IL-21 and IL-15 in regulating CD8+ T cell expansion and function

Abstract: Interleukin (IL)-21 is the most recently recognized of the cytokines that share the common cytokine receptor γ chain (γc), which is mutated in humans with X-linked severe combined immunodeficiency. We now report that IL-21 synergistically acts with IL-15 to potently promote the proliferation of both memory (CD44high) and naive (CD44low) phenotype CD8+ T cells and augment interferon-γ production in vitro. IL-21 also cooperated, albeit more weakly, with IL-7, but not with IL-2. Correspondingly, the expansion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
549
15
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 654 publications
(611 citation statements)
references
References 36 publications
41
549
15
2
Order By: Relevance
“…This suggested that the IL-21 was acting through a CD8 T cell-dependent mechanism. Most recently, IL-21 has been reported to act synergistically with IL-15 to directly promote Ag-independent clonal expansion of CD44 high and CD44 low CD8 T cells (23). The same authors also observed a marked defect in Ag-specific CD8 T cell cytolytic activity after response to viral challenge in IL-21R Ϫ/Ϫ mice.…”
Section: Il-21 Promotes Differentiation Of Naive Cd8 T Cells To a Unisupporting
confidence: 54%
See 1 more Smart Citation
“…This suggested that the IL-21 was acting through a CD8 T cell-dependent mechanism. Most recently, IL-21 has been reported to act synergistically with IL-15 to directly promote Ag-independent clonal expansion of CD44 high and CD44 low CD8 T cells (23). The same authors also observed a marked defect in Ag-specific CD8 T cell cytolytic activity after response to viral challenge in IL-21R Ϫ/Ϫ mice.…”
Section: Il-21 Promotes Differentiation Of Naive Cd8 T Cells To a Unisupporting
confidence: 54%
“…2a); however, synergistic interactions have been reported for IL-21 and other IL-2 family members (19,23). Although we do not add exogenous IL-2 to the cultures, CD8 T cells are capable of transient autocrine IL-2 production upon activation (10,27,28).…”
Section: Optimal Il-21 Induction Of Cd8 T Cell Cytolytic Activity Reqmentioning
confidence: 99%
“…Our findings show not only a higher proliferative potential of BM CMV-specific T cells but also the persistence of a specific T CM population upon in vitro expansion in the presence of IL-2 and IL-7. Ongoing studies focusing on conditions to more efficiently expand T CM by using cytokines, such as IL-15 and IL-21 [32], and depletion of regulatory T cells [33] hold promise for achieving the rapid generation of high frequencies of T CM for more efficient adoptive T cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…CD62L hi Tcm cells generated in the presence of IL-15 have been shown to eradicate large, established tumors after vaccination with a recombinant virus and administration of IL-2, while cells of a CD62L lo effector/Tem phenotype were ineffective [9]. Similarly, treatment with IL-15 and/or IL-21, factors that support the expansion of Tcm cells, led to improved anti-tumor activity [16][17][18]. Lowering the antigen concentration or reducing the culture duration also promoted the development of Tcm-like cells, which had reduced effector function but remained able to destroy established EG7 tumors [19].…”
Section: Discussionmentioning
confidence: 99%